2014
DOI: 10.5430/ijfr.v5n4p196
|View full text |Cite
|
Sign up to set email alerts
|

Examining Linkages between Saudi Stock Market (TASI) and Selected Stock Markets Indices

Abstract: This study makes an endeavor to examine the existence of linkages between Saudi Stock Market Index (TASI) and the bigwig stock markets indices, namely, US, UK, Japan and Gulf Cooperation Council (GCC). Data are culled and collated on a weekly basis commencing from 01/07/2004 to 31/12/2008 for the Period-I (This phase cover substantial economic boom period in Saudi Arabia) and from 01/01/2009 to 31/07/2013 for the Period-II (This duration encapsulates major restructuring in the Saudi stock market sectors). Sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…Having applied ARCH, GARCH, and EGARCH, it was found that the dynamic traits of the Jordanian stock market were effectively captured by the symmetric ARCH/GARCH models, whereas the EGARCH model failed to yield any evidence of existing leverage effects in stock returns. Rehman and Hazazi (2014) point to certain stock markets building a rapport over the years, including those of the US, Japan, the UK, and the GCC. They also indicated that the Saudi index had gradually seen a decrease in volatility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Having applied ARCH, GARCH, and EGARCH, it was found that the dynamic traits of the Jordanian stock market were effectively captured by the symmetric ARCH/GARCH models, whereas the EGARCH model failed to yield any evidence of existing leverage effects in stock returns. Rehman and Hazazi (2014) point to certain stock markets building a rapport over the years, including those of the US, Japan, the UK, and the GCC. They also indicated that the Saudi index had gradually seen a decrease in volatility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the contrary, Rehman and Hazazi (2014) explain that this co-movement among economies may increase homogeneity in market performance in reaction to international financial impacts. This might cause a peril from some events such as a credit crunch, capital flight, a contagion effect, and so on.…”
Section: Introductionmentioning
confidence: 97%
“…Over the last three decades, emerging markets have raised profits enormously, for they provide many investment opportunities in financial sectors (Rehman and Hazazi 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The country"s stock market history dates to 1934, when trading practices were unofficial until established officially in 1983 (Asiri & Alzeera, 2013). The Saudi stock market is still under development as compared to advanced countries" stock markets; although it holds the 13th position in the list of countries with the strongest economy (Rehman, Hazazi, & Programe, 2014). Few of the previous studies have compared the volume of Saudi economy at its establishment with advanced economy (Rehman, Khan, & Khokhar, 2015;Syed & Bajwa, 2018).…”
Section: Introductionmentioning
confidence: 99%